2008
DOI: 10.1002/ana.21398
|View full text |Cite
|
Sign up to set email alerts
|

Different features of histopathological subtypes of pediatric focal cortical dysplasia

Abstract: Different histopathological types of mMCD/FCD have distinct clinical and imaging characteristics. The ability to predict the subtype before surgery could influence surgical planning. Invasive electroencephalographic study should be considered when mMCD/FCD type I is expected based on noninvasive tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
259
3
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(299 citation statements)
references
References 52 publications
23
259
3
10
Order By: Relevance
“…Focal cortical dysplasia type I lesions have highly idiosyncratic presentations and are usually more diffuse than type II lesions, making them the most challenging ones to be detected by structural imaging methodology. [28][29][30] In addition to the accurate definition, delineation of the boundaries of type I focal cortical dysplasia is also difficult, as the microscopically dysplastic lesion may extend well beyond the margins defined by the MRI-visible abnormality (in MRIpositive cases), [30][31][32] even with the use of highresolution dedicated epilepsy MRI protocols and review of the images by expert neuroradiologists. 26,32 Our finding of MRI-negative patients with hippocampal sclerosis is also consistent with previous literature that up to 30% of patients with hippocampal sclerosis may have normal findings on conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Focal cortical dysplasia type I lesions have highly idiosyncratic presentations and are usually more diffuse than type II lesions, making them the most challenging ones to be detected by structural imaging methodology. [28][29][30] In addition to the accurate definition, delineation of the boundaries of type I focal cortical dysplasia is also difficult, as the microscopically dysplastic lesion may extend well beyond the margins defined by the MRI-visible abnormality (in MRIpositive cases), [30][31][32] even with the use of highresolution dedicated epilepsy MRI protocols and review of the images by expert neuroradiologists. 26,32 Our finding of MRI-negative patients with hippocampal sclerosis is also consistent with previous literature that up to 30% of patients with hippocampal sclerosis may have normal findings on conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies specifically assessing MRI features of CD correlated with pathology and outcome in pediatric (or mostly pediatric) patients, with the investigators using more modern pathological classification systems. 14,16,17,19,33 Most of these studies also included CD in the temporal lobe associated with hippocampal sclerosis (ILAE Type IIIa), 3 which complicates evaluation of the imaging, pathology, and outcome correlations in this population. For our study, to provide the most homogeneous cohort for evaluation, we excluded these patients, as well as patients with other brain abnormalities and CD (Types IIIb, IIIc, and dual pathology).…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI findings and outcome assessments have been described in some children with CD, 15,16,19,20 the underlying pathological basis for imaging findings in a consistent cohort of children has been incompletely assessed. We could find no prior study in which a resection region-specific evaluation was used to directly relate histopathological and imaging findings in pediatric subjects.…”
mentioning
confidence: 99%
“…A recent study 13 showed that children with FCD Type IIB had more localized ictal electroencephalographic patterns and MRI changes, while hippocampal sclerosis and hypoplasia/atrophy were common in FCD Type I. The same authors 14 found that incomplete resection of the FCD is the main predictor of poor postsurgical outcome, because the only significant predictor of surgical success was completeness of surgical resection.…”
Section: Malformations Due To Abnormal Neuronal and Glial Proliferatimentioning
confidence: 98%
“…Most patients have medically intractable partial epilepsy, frequently with disabling motor and secondary generalized seizures, including status epilepticus. These patients often are correctly diagnosed before surgery, but surgical results still are not fully satisfactory in many of them.A recent study 13 showed that children with FCD Type IIB had more localized ictal electroencephalographic patterns and MRI changes, while hippocampal sclerosis and hypoplasia/atrophy were common in FCD Type I. The same authors 14 found that incomplete resection of the FCD is the main predictor of poor postsurgical outcome, because the only significant predictor of surgical success was completeness of surgical resection.…”
mentioning
confidence: 96%